2013
DOI: 10.17221/55/2011-pps
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of gut proteases in the fig tree skeletoniser moth, Choreutis nemorana Hübner (Lepidoptera: Choreutidae)

Abstract: The biochemical properties of proteases from the digestive system of the fig tree skeletonizer moth, Choreutis nemorana, were determined. Gut extracts of C. nemorana larvae were analysed using different specific peptide substrates and proteinase inhibitors. The optimal pH and temperature for proteolytic activities using azocasein as substrate were obtained as pH 11 and 45°C, respectively. In the case of N-benzoyl-l-arg-p-nitroanilide as substrate, the enzyme showed the maximum tryptic activity at pH 11. The ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The mid gut region of insect digestive system comprises of digestive proteases which catalyses the breakdown of proteins into small molecules [20]. Protease inhibitors are proficient in interfering with digestive enzymes of insect gut and hence are able in controlling them [21]. JSTI (Jack fruit Seed Trypsin Inhibitor) has effectively shown insecticidal activity against proteases of larval mid gut [18].…”
Section: Introductionmentioning
confidence: 99%
“…The mid gut region of insect digestive system comprises of digestive proteases which catalyses the breakdown of proteins into small molecules [20]. Protease inhibitors are proficient in interfering with digestive enzymes of insect gut and hence are able in controlling them [21]. JSTI (Jack fruit Seed Trypsin Inhibitor) has effectively shown insecticidal activity against proteases of larval mid gut [18].…”
Section: Introductionmentioning
confidence: 99%
“…Franco et al, (2004) reported that Enzymatic assays using gut extracts from larval and adult boll weevil have demonstrated the presence of digestive serine proteinase-like activities and in vitro assays showed that soybean Kunitz trypsin inhibitor (SKTI) was able to inhibit these enzymes. Gholamzadeh et al, (2013) investigated that, the Proteolytic activity of azocasein as a protein substrate in the gut of C. nemorana was 7.267 ± 0.37 μmol/min/mg protein. In addition, the trypsin and chymotrypsin activity was 1.53 ± 0.03 and 1.42 ± 0.1 μmol/min/mg protein, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were incubated at 4 °C for 30 min, the centrifuged at 10,000× g for 10 min and 100 µL of the supernatant mixed with NaOH 1 M (100 µL). The activity of protease was expressed as µmol dye/min/mg protein using the extinction coefficient of the chromogenic azo group produced by the cleavage of casein [18].…”
Section: Methodsmentioning
confidence: 99%